Modelling of connection behaviour for progressive collapse analysis. (October 2015) - Stylianidis, P.M.; Nethercot, D.A.
Abstract: The structural robustness of frame structures depends to a considerable extent on the ability of the connections between the main structural elements to transmit the sorts of loading generated following an initial structural damage while delivering the deformations needed to arrest progressive collapse through dissipation of the collapse energy. Therefore, connection performance is, arguably, the most important feature of the problem and accurate modelling of the connection behaviour under the sorts of conditions experienced during progressive collapse is an essential component for any realistic analysis. Based on the component method principles of EC3 and EC4, a mechanical approach for describing the behaviour of bare steel and composite connections for use in progressive collapse analyses is developed herein. Explicit expressions covering the full range of loading – including interaction between the connection bending moments and beam axial load – and problem variables likely to be encountered in practice are derived. Those expressions can be applied in a step-by-step consideration for tracing connection nonlinear behaviour up to failure. The model is carefully validated against both available tests and results obtained from rigorous numerical analyses. Highlights: The behaviour of steel and composite connections during progressive collapse is considered. A new mechanical approach for modelling the connection behaviour is derived. The model accounts explicitly for the basic features of performance. The response can be accurately described using accessible spreadsheet calculations. The model is validated against available tests and detailed numerical analyses.